The sense of brown ethnicity, affect and performance - Muñoz, José Esteban (Duke University Press, 2020)
The Brown Commons -- Feeling Brown: Ethnicity and Affect in Ricardo Bracho's The Sweetest Hangover (and -- Other STDs) -- The Onus of Seeing Cuba: Nilo Cruz's Cubanía -- Meandering South: Isaac Julien and The Long Road to Mazatlán -- "Chico, What Does It Feel Like to Be a Problem?": The Transmission of Brownness -- The Vulnerability Artist: Nao Bustamante and the Sad Beauty of Reparation -- Queer Theater, Queer Theory: Luis Alfaro's Cuerpo Politizado (2000) -- Performing the Bestiary: Carmelita Tropicana's With What Ass Does the Cockroach Sit?/Con Que Culo se Sienta la Cucaracha? -- Performing Greater Cuba: Tania Bruguera and the Burden of Guilt -- Wise Latinas -- Brown Worldings: Jose Rodriguez-Soltero, Tania Bruguera, and María Irene Fornés -- The Sense of Wildness: The Brown Commons after Paris Burned -- Vitalism's Afterburn: The Sense of Ana Mendieta
Includes bibliographical references and index. - Description based on print version record
Keywords: Hispanic Americans in the performing arts; Hispanic Americans / Ethnic identity; Performance art; Queer theory; Art and race